Print Media As A Vehicle Of Narrative Building: A Multimodal Discourse Analysis Of Political Caricatures - Ms. Aisha Umer , Dr. Ijaz Asghar , Dr. Zarina Qasim , Dr. Naveed Nawaz Ahmad , Amber Hassan (Migration Letters, 2024)
This article is based on the analysis of political caricatures in Pakistani English newspaper regarding some hot issues in Pakistani politics during 2016-18 including Panama Leaks, News-gate scandal and Political sit-ins. This research aims to uncover the hidden purpose of print media through multimodal analysis of selected political caricatures. The study was conducted using multimodal discourse analysis (Kress & Leeuwen, 2006) under systemic functional grammar to discuss the role of different modes (visual and communicative) integrated together to understand the message which the editor wants to portray behind the caricatures. The paper analyzed selected caricatures from mainstream Pakistani e-newspapers “The Nation”. Six caricatures were selected by the re[1]searcher for analysis of the caricatures. The caricatures were explored using Kress and Leeuwen’s (2006) three meta-functions of visual grammar. The results give insights to the applicability of multimodality on political caricatures and it also reveals the enhancement of semantic quality for the caricatures through the integration of various modes. The study also discovered that editors of newspaper used visual language to communicate and subject the public perception regarding one political ideology. Furthermore, the print media criticize political parties whose policies are not in the best interests of the people.